Kinerja Polisi Satuan Lalu Lintas (Satlantas) Di Polres Wajo - Rahmawati, Rahmawati; Ansari, Muh Isa; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
Performance is one of the factors that determine the achievement of organizational goals. Based on this, this research purposed to determine the performance of the police in providing driving license (SIM) issuance services and the factors that influenced performance in providing Satlantas driving license issuance services at the Wajo Police. This research method used data collection through observation, interviews and documentation. The informants in this study were 8 people. The data that had been obtained from the research results are processed using descriptive qualitative analysis techniques. The results of this study showed the performance of  Police in the service of issuing a driving license (SIM) at the Wajo Police Satlantas office seen from the aspect of service quality where the service was passed by taking queue numbers that could be taken offline or online. It made easier for SIM applicants, the aspect of service responsiveness  had provided satisfaction with the community but the friendliness of the officers was still less, the responsiveness aspect had implemented the Standard Operating Procedure (SOP), and the accountability aspect was in accordance with its accountability but it constrainted on facilities and infrastructure but it was still be controlled properly.Keywords: Performance, driving license (SIM) Service